Influence of School Conduciveness on learners’ Academic Performance in Public Secondary Schools in Murang'a and Kirinyaga Counties in Kenya - Stephen Weru Njega; Johannes Njagi Njoka; Cathrine Waithera Ndung’u (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2020)
The influence of school conduciveness on learners’ academic performance is not clearly known and documented in the world and especially in Kenya. However, the school conduciveness being a psychosocial variable significantly compliments the teaching and learning process. School conduciveness is believed to play an instrumental role on the acceptance, understanding and internalization of the learnt content by the learners. The purpose of this study was to assess the influence of the school conduciveness on learners’ academic performance in public secondary schools in Murang’a and Kirinyaga Counties in Kenya. The study was guided by two objectives which were to; assess how students’ attitudes towards schooling influences academic performance, and to examine how the psychosocial support systems influences academic performance in public secondary schools in Murang’a and Kirinyaga counties in Kenya. The study tested the null hypothesis Ho1: There was no significant difference between the attitudes of learners towards school psychosocial variables by gender, school category and county of origin of the institution from the two counties. The study adopted the correlational research design. The target population was 5879 consisting of all the form three students in national and extra-county public schools in Murang’a and Kirinyaga counties in Kenya. The national schools in the counties were purposively sampled, while a sample size of 7 extra-county schools was selected using the Gay’s sampling criteria of 10-30%, where the upper limit of 30% of the 22 extra-county schools was used. The Yamane’s formula was used to select a sample size of 412 students from the target population. The study selected respondents in three categories based on their academic performance forming three cadres; top cadre, middle cadre and bottom cadre. A questionnaire with 5-point Likert scale was used to collect data. Reliability of the instrument was ascertained using the Cronbach’s reliability test which yielded r=0.808 which was higher than the basic recommended threshold of 0.7 proposed by Kerlinger. The findings showed that the students in national and extra-county schools scored school conduciveness highly at x̄=71.24%. This school conduciveness correlates significantly with academic performance with Pearson’s correlation coefficient r=0.176, with a p-value=0.000 at α =.05level of significance. From the study findings, it is concluded that school conduciveness significantly influences learners’ academic performance. The study recommends that there is need to strengthen and modify school conduciveness by ensuring the psychosocial support systems are appropriately catered for during the teaching and learning processes.